Dual pathways of tRNA hydroxylation ensure efficient translation by expanding decoding capability - Sakai, Yusuke (Nat Commun, 2019)
In bacterial tRNAs, 5-carboxymethoxyuridine (cmo(5)U) and its derivatives at the first position of the anticodon facilitate non-Watson–Crick base pairing with guanosine and pyrimidines at the third positions of codons, thereby expanding decoding capabilities. However, their biogenesis and physiological roles remained to be investigated. Using reverse genetics and comparative genomics, we identify two factors responsible for 5-hydroxyuridine (ho(5)U) formation, which is the first step of the cmo(5)U synthesis: TrhP (formerly known as YegQ), a peptidase U32 family protein, is involved in prephenate-dependent ho(5)U formation; and TrhO (formerly known as YceA), a rhodanese family protein, catalyzes oxygen-dependent ho(5)U formation and bypasses cmo(5)U biogenesis in a subset of tRNAs under aerobic conditions. E. coli strains lacking both trhP and trhO exhibit a temperature-sensitive phenotype, and decode codons ending in G (GCG and UCG) less efficiently than the wild-type strain. These findings confirm that tRNA hydroxylation ensures efficient decoding during protein synthesis.